Chinese herbal medicine xuebijing injection for acute pancreatitis: An overview of systematic reviews - Zhu, Fengya; Yin, Shao; Zhou, Li; Li, Zimeng; Yan, Hui; Zhong, Yue; Wu, Xiaohan; Luo, Biao; Yang, Lanying; Gan, Daohui; Deng, Lvyu; Che, Deya; et al. (Frontiers in Pharmacology, 2022)
Background: At present, a number of systematic reviews (SRs) on Xuebijing injection (a patent in China) in the treatment of acute pancreatitis (AP) or severe acute pancreatitis (SAP) have been published. However, the quality of evidence is uneven and has not been comprehensively evaluated. Aim: We evaluated the efficacy of Xuebijing injection for AP/SAP through an overview of SR, and to provide a scientific basis for its effectiveness and safety. Methods: We searched Cochrane Library, Embase, PubMed, SinoMed, CNKI, Wanfang, and VIP comprehensively. The retrieval period from inception to 30 November 2021, and the two reviewers independently complete the literature retrieval, data extraction and evaluation. The Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2) and the Preferred Reporting Item for Systematic Review and Meta-analysis (PRISMA) were used to evaluate the methodological quality and reporting quality of the SRs, respectively. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool was used to evaluate the quality grading of outcomes and the risk of bias in SRs was evaluated by ROBIS Tool. Finally, the RCTs involved in SRs were synthesized. Stata15.1 was used for quantitative analysis of total effectiveness rate, time until relief of abdominal pain, time until relief of abdominal distension, and serum amylase level. Results: Nine eligible SRs were included, including 92 RCTs and 6,837 participants. The quality of SRs was relatively good, and the manuscript structures were relatively complete. However, the methodological quality of SRs was low or critically low. RoB rated 5 SRs as low risk of bias and 4 SRs as high risk of bias. In GRADE, a total of 47 results were included in the 9 SRs, of which 5 results (10.64%) were moderate quality, 22 results (46.81%) were low quality, and 20 results (42.55%) were very low quality. The results of data synthesis showed that Xuebijing injection combined treatment increased the total effectiveness rate of AP patients (RR = 1.19, 95% CI 1.17–1.23, p < 0.0001), and there was no heterogeneity between studies (I2 = 0.0%, p = 0.589). Compared with the control group, Xuebijing injection group shortened the abdominal pain and distension relief time in AP patients (WMD = −1.69, 95% CI −1.88–−1.50, p < 0.0001; WMD = −1.48, 95% CI −1.74–−1.23, p < 0.0001), with high heterogeneity (I2 = 84.3%, p = 0.000; I2 = 72.2%, p = 0.000). Serum amylase level was also reduced (WMD = −2.06, 95% CI −2.47–−1.64, p < 0.0001), with significant heterogeneity (I2 = 71.6%, p = 0.000). A total of one SR reported adverse drug reaction (ADR), no ADRs were observed in the control group. Conclusion: Although the quality of the evidence is not high, it can still reflect the clinical value of Xuebijing injection as an analgesic and anti-inflammatory traditional Chinese medicine in the treatment of AP/SAP. Therefore, future clinical studies should focus on the long-term efficacy and adverse reactions of drugs. Systematic Review Registration: (website), identifier (registration number).